1905 N.C. Sess. Laws 547 - (:unkn) unknown (My University, 1905)
Priv. Laws, ch. 188, § 6: That the commissioners of said town shall have authority to pass all necessary by-laws and ordinances for the proper government of the town, and to enforce the same by means of suitable fines and penalties. Among the powers specifically conferred upon the commissioners are the following: . . . to prescribe conditions under which may be sold and used fire-arms of all kinds including toy guns and pistols and air-guns, brass knuckles, loaded canes, dirks, bowie and other knives used as weapons, ammunition and fire-works, not inconsistent with the general laws of the State[.]
Keywords: TRANSFER, MANUFACTURE & POSSESSION; TRANSFER, MANUFACTURE & POSSESSION - TOYS AND EXPLOSIVES